The structural equation modeling of reading interest psycho-behavioural constructs: How are they related across different modes of reading? - Nur Hidayanto Pancoro Setyo Putro; Jihyun Lee (Program Pascasarjana Universitas Negeri Yogyakarta & HEPI, 2017)
The present study examines the relationships between the psycho-behavioral constructs underlying undergraduate students’ reading interest. The a priori framework for conceptualizing the sub-components of reading interest is based on two modes of reading (printed-text-based and also Internet-based), and three types of psycho-behavioral motives/intentions of reading (affective, cognitive, and behavioral). Participants in this study were students (M = 20.14 years old) from an Indonesian university (n = 993). Exploratory and confirmatory factor analyses show the salience of 10 factors across reading modes and psycho-behavioral domains of reading. The most accept-able SEM models that explore the relationships among the sub-components of reading interest have the student reading interest in the print mode preceded interest in reading online materials. Implications of these findings are discussed for theory development and practice.